Evaluating Usability of EMR-Integrated Triage Technologies in the Emergency Department: A Literature Review - I Gede Rendy Arizona Vallentino; Ni Luh Putu Inca Buntari Agustini; Wulandari, Ida Ayu Putri; Yustina Ni Putu Yusniarvati (Babali Publisher, 2026)
Introduction: The Emergency Department (ER) is a vital hospital unit that handles critically ill patients. The triage process determines treatment priorities, so speed and accuracy significantly impact patient safety. The implementation of Electronic Medical Records (EMR) is expected to improve triage quality. However, usability aspects such as ease of use, efficiency, error prevention, user satisfaction, and workflow compatibility still require a comprehensive review. This review aimed to explore current evidence on the usability of EMR-based triage systems in Emergency Departments and the factors influencing successful implementation.Methods: This literature review followed the PRISMA 2020 guidelines. Articles were searched through PubMed, ScienceDirect, and Google Scholar using the terms “usability,” “triage,” “electronic medical record,” and “emergency room.” Included articles were original studies published in English between 2020 and 2025 that addressed the validity, reliability, or usability aspects of an EMR-based triage system in the ED. Review articles, conference abstracts, and irrelevant studies were excluded. From the selection process, 15 articles were selected for analysis.Results: EMR-based triage instruments, such as EMOnco (Brazil) and CETS (China), are valid and reliable. Digital systems such as eResus, MUST-Plus, and CDSS improve documentation, accuracy, and patient safety. Mobile applications have yielded mixed results: MEDIC faces learnability challenges. At the same time, CoSMoS is easy to use despite limited EMR integration. User satisfaction increases when systems support team communication and transparency, but barriers such as low computer literacy, alert fatigue, resistance, and documentation burden persist.Conclusion: EMR-based triage technology in the ER has the potential to improve efficiency, accuracy, and patient safety, but its effectiveness depends heavily on usability. Successful implementation requires a user-centered design approach, ongoing training, and periodic usability evaluation.